Prevalence of personality disorders and its association with post-treatment relatives in polymonsumident patients of substances in a residential treatment unit - Nieto-Preciado, Daniela (2017)
Introduction: Personality disorders that are comorbid to substance use lead to relapse and functional deterioration. Early evaluation allows for the formulation of appropriate therapeutic goals. Objective: To establish the frequency of relapse to four months of follow-up in patients consuming substances with personality disorders. Method: The Structured Clinical Interview for DSM-IV Axis II Personality Disorders (SCID II) was used to evaluate personality disorders and urine substance screening to evaluate abstinence. Results: A total of 33 patients were evaluated, and 36.4% presented personality disorders; The antisocial disorder had the highest prevalence. Patients with personality disorders had relapse in consumption. Conclusion: Treatments for substance use should include interventions for personality disorders and other comorbidities to prolong substance withdrawal.